Fortification of milk with phytosterol and its effect on sensory and physicochemical properties - Nagarajappa V.; Battula S.N.; Arora S.; Naik L.N. (Irish Journal of Agricultural and Food Research, 2018)
Phytosterols are a group of lipophilic steroid alcohols found in plants, which have been shown to lower cholesterol when supplemented in the diet. A commercial phytosterol preparation was added to milk in the form of an oil-in-water emulsion. For the preparation of an emulsion, diacetyl tartaric acid ester of mono- and diglycerides was used as an emulsifier and butteroil was used as a source of fat. Three emulsion formulations, i.e. A (8% phytosterols), B (10% phytosterols) and C (12% phytosterols), were prepared in which the levels of emulsifier (6.5%) and butteroil (10%) were kept constant, and each emulsion was added to milk at a rate of 5% (w/w). Based on sensory evaluation, B-emulsion formulation was selected for fortification of milk. The phytosterol content of the fortified milk determined by reverse-phase high-performance liquid chromatography was 410.8 mg/100 g. No significant loss in the initial content of phytosterol was observed after 1 week of storage. Sensory and physicochemical analyses indicated that significant differences were not observed between control and fortified milk samples up to 7 days of refrigerated storage. The present study suggests that it is feasible to add phytosterol as a functional ingredient in milk in the form of water-soluble emulsion to enhance health benefits of consumers. Two servings of such fortified milk per day provide almost the entire recommended daily requirement of phytosterol.